THE INFLUENCE OF INFORMATION TECHNOLOGIES ON MODERN LEGAL EDUCATION - Lazarchuk, Hanna (Sworld-Us Conference proceedings, 2023)
The paper examines the influence of information technologies on legal education, the advantages of introducing such technologies into the educational process, as well as the importance of innovative teaching methods in the process of legal education